Inovasi Karya Nyata Dalam Mengembangkan Dunia Digital Pada Masyarakat Kelurahan Sawah Lebar Baru - Jesika Yolinda; Sherly Cahyani; Zulhirma Sofianti; Diya Pitaloka (Jurnal Inovasi Kerja Nyata, 2026)
The rapid development of digital technology requires people from all walks of life to be able to adapt and make the best possible use of technology. This study aims to describe the implementation of practical innovations in efforts to develop the digital competencies of the community in Sawah Lebar Baru RT 26. The method used is a qualitative descriptive approach through observation, interviews and documentation of digital empowerment activities carried out within RT 26. The research findings indicate that practical innovations—such as digital literacy training, the introduction of online public service applications, and the creation of community digital information media—have enhanced the community’s understanding and ability to access and utilise technology. Furthermore, these innovations have encouraged greater resident participation in digital activities and strengthened communication amongst residents via online platforms. Challenges encountered included low initial digital literacy among some residents, limited facilities, and a lack of ongoing support. Overall, this practical innovation programme has proven to have a positive impact on the development of the digital culture of the community in Sawah Lebar Baru RT 26. These efforts can serve as a model for technology-based empowerment with the potential to be implemented in other neighbourhoods.